Development of ethno-mathematics of Al-Quran, Al hadith and Jawi scripts for computer security / A.Faizul Shamsudin and Mohammad Alinor - Shamsudin, A.Faizul; Alinor, Mohammad (Division of Research and Industry Linkages, UiTM Melaka, 2014)
Personal data is constantly being compromised not just by the normal identity thefts but also abnormal attacks. A continuous search on new paradigm of nonparametric cryptographs led to the discovery of ethno-mathematics for substitution block- cipher boxes. The objects based on extracted Al-Qur'an and AI-Hadith symbols by use of ethno-mathematical functions. The extracted objects were insufficient to build the 256 bit block-ciphers. The development of expanding objects from Jawi Scripts may fill the gap for a 256 bit block-cipher. Initial tests for algebraic attacks indicate Ethno-Mathematical Block Cipher resistance to be better than the random parametric Khazad and Annubis Block Ciphers.